2008
DOI: 10.1177/0021955x08090420
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Foams as Core Materials Used in Vacuum Insulation Panel

Abstract: This work examines the foam density, average cell sizes, and cell structure of four polystyrene (PS) blended with calcium carbonate (CaCO 3 ) or low density polyethylene (LDPE) at various ratios. The PS/CaCO 3 and PS/LDPE are foamed by carbon dioxide (CO 2 ) under supercritical conditions. CaCO 3 and LDPE can strongly influence the foam density, average cell sizes, and cell structure of PS foams. Based on the result of PS/CaCO 3 foams and PS/LDPE foams, the thermal conductivity of large porous PS foams as core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…[64] demonstrated that PUR-core VIPs have worst performance because of high outgassing rates. [29] showed that the use of low density polyethylene with polystyrene at some temperatures may provide thermal conductivities as low as 6.5 mW/mK, which, however, is still higher than those demonstrated by silica VIPs. [32] proposed by using double envelopes and three-sided sealing envelopes with getters with PUR foams as cores for VIPs.…”
Section: Other Vacuum Insulation Panel Types For Buildingsmentioning
confidence: 95%
See 1 more Smart Citation
“…[64] demonstrated that PUR-core VIPs have worst performance because of high outgassing rates. [29] showed that the use of low density polyethylene with polystyrene at some temperatures may provide thermal conductivities as low as 6.5 mW/mK, which, however, is still higher than those demonstrated by silica VIPs. [32] proposed by using double envelopes and three-sided sealing envelopes with getters with PUR foams as cores for VIPs.…”
Section: Other Vacuum Insulation Panel Types For Buildingsmentioning
confidence: 95%
“…In recent years, research interest in VIPs increased, as the studies covered such topics as thermal conductivity and gas pressure in VIPs [23][24][25][26], analytical and optimisation models [27,28], application of various materials in VIP manufacturing [1,[29][30][31][32] and applications of VIPs in building construction became growing areas of research [3,20,33,34].…”
Section: Vacuum Insulation Panel Overviewmentioning
confidence: 99%
“…By using equation (6), the relationship between the calculated values of k g as function of density is presented in Figure 5. The extrapolated, dashed line in Figure 5 for small densities q reaches, as expected, the thermal conductivity k g of still air, around 26 mW/mÁK.…”
Section: White 1st Generation Ps Foammentioning
confidence: 99%
“…The search for lightweight, nanometric, pore materials at low production costs and with suitable mechanical properties has been a challenge for the scientific community. [4][5][6][7][8][9][10][11][12] Nanostructured foam materials can efficiently suppress gas conduction (by the so called Knudsen effect 13 ) thus being less sensitive to the inherent internal gas pressure increase in VIPs. The recent development of polymeric foams has yielded results especially in terms of cell size reduction, but its corresponding foam densities still remain too high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation